2000
DOI: 10.1287/orsc.11.3.270.12502
|View full text |Cite
|
Sign up to set email alerts
|

When Market Information Constitutes Fields: Sensemaking of Markets in the Commercial Music Industry

Abstract: In this paper we outline a key mechanism through which organizational fields are constituted. We suggest that in competitive fields, the market serves as a magnet around which groups of actors consolidate, and that cognition of markets occurs through the creation, distribution, and interpretation of a web of information about the “market.” To illustrate our theory, we present a case study of the Billboard music chart from the commercial music industry to show that changes in either scope, methodology, or polit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
212
0
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(227 citation statements)
references
References 18 publications
6
212
0
9
Order By: Relevance
“…Previous examinations of sensemaking have sought to argue its existence within organizations (Anand & Peterson, 2000;Bogner & Barr, 2000;Gioia & Thomas, 1996) with limited empirical evidence confirming its relationship with organiza tional performance (Thomas et al, 1993). Only recently have researchers begun to examine the role of sensemaking in new product (Akgun, Lynn, & Yilmaz, 2006) and interfirm outcomes (Johnson, Sohi, & Grewal, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Previous examinations of sensemaking have sought to argue its existence within organizations (Anand & Peterson, 2000;Bogner & Barr, 2000;Gioia & Thomas, 1996) with limited empirical evidence confirming its relationship with organiza tional performance (Thomas et al, 1993). Only recently have researchers begun to examine the role of sensemaking in new product (Akgun, Lynn, & Yilmaz, 2006) and interfirm outcomes (Johnson, Sohi, & Grewal, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A commonly held view is that reputation involves "being known for something" (Jensen & Roy, 2008;Lange et al, 2011) and is based on an actor's accomplishments and history (Barron & Rolfe, 2012;Weigelt & Camerer, 1988). 1 Previous studies that have examined the external signals of reputation (Anand & Peterson, 2000;Carter et al, 1998;Ebbers & Wijnberg, 2012;Philippe & Durand, 2011) suggest that reputation reduces uncertainty about an actor's future behavior, which enables evaluators (i.e., an audience) to assess actors (Spence, 1973). A positive reputation is beneficial because it reduces uncertainty and provides reassurance of an actor's value.…”
Section: Audience-specific Reputationsmentioning
confidence: 99%
“…A great deal of work in the last two decades has shown that institutional entrepreneurs may arise to question institutional arrangements (DiMaggio, 1988), resisting them strategically (Oliver, 1991;Ang & Cummings, 1997), disrupting and deinstitutionalizing them (Ahmadjian & Robinson, 2001;Oliver, 1992), and reconstructing them to suit the desires of different actors (Anand & Peterson, 2000;Hargadon & Douglas, 2001;Zilber, 2002).…”
mentioning
confidence: 99%